THE EFFECT OF THE ADDITION OF GINGER (Curcuma xanthorrhiza ROXB) TO FEED TO TOTAL ERYTHROCYTES, HEMATOCRIT, HEMOGLOBIN and GROWTH OF CATFISH (Mystus nemurus) - Feri Yulistia; Iesje Lukistyowati; Morina Riauwaty (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This research was done in March - April 2014 in Fish Disease Parasite and Laboratories and an Experiment of the Faculty of Fisheries and Marine Science University of Riau. The purpose of this research is to know the influence of the addition of curcuma on feed to the total of erythrocytes , hematocrit , hemoglobin and the growth of catfish. A research method used is the design of random complete with one factor which feed containing curcuma with four standard treatment consists of , P0: control without given ) curcuma solution , the P1 ( curcuma solution with a dose of 2 g/kilogram feed ) , the P2 ( curcuma solution with a dose of 4 g/kilogram feed ) , the P3 ( curcuma solution with a dose of 6 g/kilogram feed ). The results of research shows that the addition of a solution on feed curcuma doesn’t impact the condition of fish blood because of poor environmental conditions. It can increase the growth of absolute weight catfish .The total erythrocytes is ranged between 1,25-1,91 mm3/ million cells , hematocrit 13,8-18,5 % and the percentage of hemoglobin 3,9-4,2 g/dL.Keywords: River catfish (Mystus nemurus), ginger, blood catfish